Interactions between soil properties, agricultural management and cultivar type drive structural and functional adaptations of the wheat rhizosphere microbiome to drought. (31st May 2021) - Breitkreuz, Claudia; Herzig, Laura; Buscot, François; Reitz, Thomas; Tarkka, Mika
Summary: Rhizosphere microbial communities adapt their structural and functional compositions to water scarcity and have the potential to substantially mitigate drought stress of crops. To unlock this potential, it is crucial to understand community responses to drought in the complex interplay between soil properties, agricultural management and crop species. Two winter wheat cultivars, demanding and non‐demanding, were exposed to drought stress in loamy Chernozem and sandy Luvisol soils under conventional or organic farming management. Structural and functional adaptations of the rhizosphere bacteria were assessed by 16S amplicon sequencing, the predicted abundance of drought‐related functional genes in the bacterial community based on 16S amplicon sequences (Tax4Fun) and the activity potentials of extracellular enzymes involved in the carbon cycle. Bacterial community composition was strongly driven by drought and soil type. Under drought conditions, Gram‐positive phyla became relatively more abundant, but either less or more diverse in Luvisol and Chernozem soil respectively. Enzyme activities and functional gene abundances related to carbon degradation were increased under drought in the rhizosphere of the demanding wheat cultivar in organic farming. We demonstrate that soil type, farming system and wheat cultivar each constitute important factors during the structural and/or functional adaptation of rhizobacterial communities in response to drought.